2007
DOI: 10.1007/s10585-007-9068-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel hyperthermia for metastatic bone tumors with magnetic materials by generating an alternating electromagnetic field

Abstract: We have developed a novel hyperthermic treatment modality using magnetic materials for metastatic bone tumors. The purpose of this study is to show the results of novel hyperthermia for metastatic bone tumors. This novel hyperthermic treatment modality was used for 15 patients with 16 metastatic bone lesions. In seven lesions, after curettage of the metastatic lesion followed by reinforcement with a metal intramedullary nail or plate, calcium phosphate cement (CPC) containing powdery Fe3O4 was implanted into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 30 publications
0
54
1
2
Order By: Relevance
“…For example, Kim and co-workers [7] have obtained microspheres of Fe 3 O 4 encapsulated with chitosan as a MRI image contrast, while Jain and co-workers [8] obtained magnetic nanoparticles coated with Oleic-Pluronic for sustained delivery of cancer agents. Matsumine and co-workers [9] have developed a new hyperthermic treatment modality using magnetic materials (calcium phosphate cement containing Fe 3 O 4 ) for metastatic bone tumors. In this sense, biological molecules are important to change the magnetic component into a bio-inert composite.…”
mentioning
confidence: 99%
“…For example, Kim and co-workers [7] have obtained microspheres of Fe 3 O 4 encapsulated with chitosan as a MRI image contrast, while Jain and co-workers [8] obtained magnetic nanoparticles coated with Oleic-Pluronic for sustained delivery of cancer agents. Matsumine and co-workers [9] have developed a new hyperthermic treatment modality using magnetic materials (calcium phosphate cement containing Fe 3 O 4 ) for metastatic bone tumors. In this sense, biological molecules are important to change the magnetic component into a bio-inert composite.…”
mentioning
confidence: 99%
“…The material was grounded on a Fritsch Pulverisette 6 (Fristsch GmbH, Idar-Oberstein, Germany) planetary mill in sealed stainless steel vials (221.69 cm 3 ) and balls (酶10 mm) under air in weight ratio 1/9 (wt. of mixture powder/wt.…”
Section: Ferrimagnetic Particlementioning
confidence: 99%
“…Kim et al [1] have obtained microspheres of Fe 3 O 4 encapsulated with chitosan as a MRI image contrast, while Jain et al [2] obtained magnetic nanoparticles coated with Oleic-Pluronic for sustained delivery of cancer agents. Matsumine et al [3] have developed a novel hyperthermic treatment modality using magnetic materials (calcium phosphate cement containing Fe 3 O 4 ) for metastatic bone tumors. In this sense, biological molecules are important to begin the magnetic component in a bio-inert composite.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of this behavior, the use of bone cement containing MNPs has been proposed for the hyperthermic treatment of bone tumors [4]. Matsumine et al [5] prepared calcium phosphate cement containing Fe 3 O 4 and conducted clinical trials to treat patients with metastatic bone lesions by hyperthermia, and reported that the patients treated by hyperthermia showed better radiographic outcomes than those treated by palliative operation.…”
Section: Introductionmentioning
confidence: 99%
“…MNFs have huge potential in biomedical applications such as cancer therapy including hyperthermia [6] and tissue regeneration [5]. Visualization of MNFs as well as accurate knowledge about the quantity of MNPs within the MNFs is crucial for effective and safe treatment planning of cancer therapy or tissue regeneration using them [5] [6].…”
Section: Introductionmentioning
confidence: 99%